(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Hotels should seek out data regarding the demographics, preferences, and needs of their target audience to create more tailored campaigns. Market research can be conducted through surveys, focus groups, or customer testimonials that help hotels gain a better understanding of their target market.